Pseudoarthrosis of unilateral cervical rib and 1st rib exostosis-presenting with supraclavicular mass and thoracic outlet syndrome - Benjamin Alex; Sanal Kumar; Rajeev K.; Suvin R.; Dhanesh S. (International Journal of Research in Orthopaedics, 2023)
Cervical rib is defined as the presence of supernumerary rib at the 7th cervical vertebrae possibly associated with mutations in Hox genes. Cervical rib may have a free end or may be fused with the first rib by bone bridge or fibrous band. However, the incidence of pseudoarthrosis of cervical rib with exostosis from the first rib is reported rarely in literature. This report documents a unilateral pseudoarthrosis of cervical rib with 1st rib exostosis presenting as a supra clavicular mass with thoracic outlet syndrome.